1998
DOI: 10.1002/bbpc.19981020410
|View full text |Cite
|
Sign up to set email alerts
|

Influences of nuclear size and shape and nuclear spin on chemical isotope effect of zirconium‐crown complex

Abstract: Zirconium isotopes were fractionated by liquid‐liquid extraction system using dicyclohexano‐18‐crown‐6. The experimental enrichment factors showed failure from the Bigeleisen‐Mayer approximation, which had been believed since their article of 1947. The nuclear size and shape and the nuclear spin result in the additional isotope effects on the Bigeleisen‐Mayer approximation. The contributions of the nuclear mass and of the field shifts of s‐orbital and d‐orbital to the chemical isotopic enrichment factors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Anomalous (non‐mass‐dependent) isotope effects may also arise from symmetry effects [e.g., Gellene , 1996] or changes of other nuclear properties upon isotopic substitution (such as nuclear spin, size or shape). The latter changes can cause isotope shifts in the electronic spectra as well as vibrational and rotational energy levels [ Bigeleisen , 1996; Fujii et al , 1998; Tiemann et al , 1982]. Moreover, stellar nucleosynthesis, radioactive decay or natural nuclear reactors (such as in Oklo, Gabon) may cause exceptional isotopic variations even in environments uninfluenced by mankind.…”
Section: Terminologymentioning
confidence: 99%
“…Anomalous (non‐mass‐dependent) isotope effects may also arise from symmetry effects [e.g., Gellene , 1996] or changes of other nuclear properties upon isotopic substitution (such as nuclear spin, size or shape). The latter changes can cause isotope shifts in the electronic spectra as well as vibrational and rotational energy levels [ Bigeleisen , 1996; Fujii et al , 1998; Tiemann et al , 1982]. Moreover, stellar nucleosynthesis, radioactive decay or natural nuclear reactors (such as in Oklo, Gabon) may cause exceptional isotopic variations even in environments uninfluenced by mankind.…”
Section: Terminologymentioning
confidence: 99%
“…Toshiyuki Fujii and his co-workers have made tremendous efforts on experimental evaluations of NVEs for isotope systems, including Ti, Sn, Zr, Ni, Zn, Gd, Nd, Cr, Sr, Te and Cd etc. 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 Meanwhile, they performed quantum chemistry calculations for a few isotope systems, such as Zn 20 21 , Ni 18 , Tl 30 and Pb 31 . Schauble 4 used quantum chemistry methods to calculate NVEs of some heavy elements (e.g., Hg, Tl) and showed that the NVE could affect isotope fractionations of heavy elements to surprising degrees.…”
mentioning
confidence: 99%
“…6 Most of these works represent the study of the reaction of an element with dicyclohexano-18crown-6 (DC18C6) crown ether. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Metal/metalloid was dissolved in aqueous solutions of HCl with different acid concentrations. Different species are predominant in these solutions depending on the HCl concentration.…”
Section: Discussionmentioning
confidence: 99%